A New Scheme to Generate Multi-Frequency Mm-Wave Signals Based on Cascaded Phase Modulator and I/Q Modulator - Mingming Zhao; Wen Zhou; Li Zhao; Jiangnan Xiao; Xinying Li; Feng Zhao; Jianjun Yu (IEEE Photonics Journal, 2019)
We propose a new scheme to generate multi-frequency vector mm-wave signals based on cascaded phase modulator and I/Q modulator by adopting independent-sideband (ISB) modulation scheme. Driven by a single frequency RF (Radio frequency) source, the phase modulator (PM) generates multi-frequency optical carriers with a constant frequency interval, which is used as optical input of the I/Q modulator. The electrical signal driving the I/Q modulator is composed of one vector-modulated single side-band (SSB) QAM signal and one unmodulated SSB RF signal, the two signals locate at different sides of zero frequency. The output of I/Q modulator contains several multi-frequencies optical side-bands and suppressed optical carriers. The optical carriers are suppressed by using the ISB modulation scheme. Two optical sidebands at different frequencies are selected by a wavelength select switch (WSS) and beaten in the photodetector (PD). The multi-frequency vector mm-wave signals are generated with high flexibility, and the frequency can be up to 400 GHz. We experimentally demonstrate 133-GHz D-band multi-frequency vector mm-wave signal over 80-km SMF-28 wireline transmission and 10-m wireless delivery with bit rate up 18.4 × 2 = 36.8 Gb/s.